Synthesis and Characterization of Quercetin-Iron Complex Nanoparticles for Overcoming Drug Resistance - Lucas Prestianni; Eric R. Espinal; Sarah F. Hathcock; Nadine Vollmuth; Pixiang Wang; Robert A. Holler; Shaoyang Liu; Brandon J. Kim; Yuping Bao (MDPI AG, 2023)
Quercetin, one of the major natural flavonoids, has demonstrated great pharmacological potential as an antioxidant and in overcoming drug resistance. However, its low aqueous solubility and poor stability limit its potential applications. Previous studies suggest that the formation of quercetin-metal complexes could increase quercetin stability and biological activity. In this paper, we systematically investigated the formation of quercetin-iron complex nanoparticles by varying the ligand-to-metal ratios with the goal of increasing the aqueous solubility and stability of quercetin. It was found that quercetin-iron complex nanoparticles could be reproducibly synthesized with several ligand-to-iron ratios at room temperature. The UV-Vis spectra of the nanoparticles indicated that nanoparticle formation greatly increased the stability and solubility of quercetin. Compared to free quercetin, the quercetin-iron complex nanoparticles exhibited enhanced antioxidant activities and elongated effects. Our preliminary cellular evaluation suggests that these nanoparticles had minimal cytotoxicity and could effectively block the efflux pump of cells, indicating their potential for cancer treatment.